4(3x-2)=2(6x-2)

Simple and best practice solution for 4(3x-2)=2(6x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x-2)=2(6x-2) equation:



4(3x-2)=2(6x-2)
We move all terms to the left:
4(3x-2)-(2(6x-2))=0
We multiply parentheses
12x-(2(6x-2))-8=0
We calculate terms in parentheses: -(2(6x-2)), so:
2(6x-2)
We multiply parentheses
12x-4
Back to the equation:
-(12x-4)
We get rid of parentheses
12x-12x+4-8=0
We add all the numbers together, and all the variables
-4!=0
There is no solution for this equation

See similar equations:

| x=80+25 | | 8-4w=-5w | | 4(1+4p)-4=48 | | (5x-2x)(x)x=3 | | 2(20x+30=420 | | -(x+4=1 | | 4h+10=-h | | 2x+12=7x-3=180 | | 4h-10=-h | | 5w+3=-18 | | -5h+7=-3(h-1) | | -4x=-9-(10x+3) | | 10y-6y-12=70.28 | | x^2−17x+64=−6 | | 8(3+5v)=-296 | | 2x-(5-x)=6(x-3)-5 | | 6−2x=3+5x | | y-8.12=7.7 | | (3x^2)-6x+9=0 | | 8v+12=3(3v+5) | | 5/n+4/(6-3n)=2n/(6-3n) | | x+3.21=7.37 | | 5/n+4/6-3n=2n/6-3n | | w+2.4=8.82 | | 12x+2=-2x+82 | | 6+6(2t-1)=3=12t | | 3x+4=24x+32 | | 2x+2=-2x+82 | | 2v+6-4v=2 | | 0=-x+-x | | -5(2x-3)+2=-43 | | 3x+23=5x |

Equations solver categories